Demand for "ikot" jeepney rides by dormitory residents in UPV Miag-ao Campus a survey. - Mana-ay, Wilfredo V., Jr
This study on "ikot" jeepney service was conducted to answer the question; What is the need for ikot jeepney rides by dormitory residents in UPV Miag-ao campus?, Specifically, the study also addressed the following problems: "To determine the potential and actual need for ikot jeepney rides by dormitory residents". "To know the availability and in availability of ikot jeepney rides" and "To determine the expenditure of a dormitory resident for ikot jeepney rides". A questionnaire and a monitoring schedule were sent out to gather data through a purposive sampling conducted on the 290 dormitory residents which yielded 91.72 or 266 respondents. The study was conducted on January 7 to February 2, 1991. The potential need for ikot jeepneys by dormitory residents according to their schedule of classes were 16.180 rides in a week. This is in assumption that students residing in the dormitories would take an ikot jeepney ride before and after their classes from the dormitory and back. The actual need for ikot jeepney rides by dormitory residents was pegged at 14.395 in 4 weeks. This referred to the number of ikot jeepney rides needed by students residing in the dormitories in order to travel from the dormitory to their classes and back. The actual need for ikot jeepney rides was the summation of both the availed and the unavailed ikot jeepney rides needed at specific time and day. In the actual need for ikot jeepney rides, the dormitory residents availed of 11,779 ikot jeepney rides but were not able to take 2,616 ikot jeepney rides. The expenditure of an individual dormitory resident on ikot jeepney fare according to the potential and actual needs were P26.03 and P67.65 in a period of one month respectively.